(untitled) (Journal of Economic Research & Business Administration, 2018)
The article contains a cross-country analysis of the effectiveness of innovation based on information from the Global Innovation Index among the countries of the Eurasian Economic Union (EAEU). The authors are exploring the possibility of using the Global Innovation Index to form reasonable conclusions about the potential for economic growth at the macro level, to identify, evaluate and compare the strengths and weaknesses of the progress in innovation and science and technology in the EAEU countries, including Kazakhstan. During the evaluation, it turned out that countries such as Switzerland, Sweden, the Netherlands, United States and a number of others have the maximum efficiency in transforming innovation resources into innovation results. From the analysis it follows that the Republic of Kazakhstan has the available resources of innovation not effectively used, at this stage the increase in costs in this area will not bring the desired result. From the analysis it follows that the problem in the EAEU countries is low demand for innovations and its inefficient structure: it is more profitable for enterprises in the EAEU countries to purchase ready-made equipment abroad than to engage in their own innovative activities. A comparative analysis of the EAEU countries in the ranking of the Global Innovation Index shows that the relatively high positions of Kazakhstan are ensured, first of all, by indicators of the development of institutions and infrastructure, with a significant lag in all measurements of the efficiency of resource use of innovation.